NATURAL GAS PRODUCTION FORECASTS IN IRAQ FOR THE PERIOD (1984-2022) USING ARIMA TIME SERIES MODELS - Soleiman, Hifaa Yousif (Journal of Economic and Economic Policy, 2026)
Objective:  This study predicted natural gas production in Iraq for the period (1984–2022) using ARIMA (Auto Regressive Integrated Moving Average) time series models. Method: The research relied on historical data of gas production to build a model capable of forecasting future trends, while analysing seasonal fluctuations and patterns. Result: The results demonstrated the efficiency of the ARIMA model in estimating future production based on past data patterns. Novelty: This study contributes to optimal planning for the exploitation of natural resources in Iraq.